(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The competition among business actors often leads to unfair competition, whether in the form of prices or non-prices. The practice of anti-dumping is an important issue in conducting international trade to achieve fair trade. Anti-dumping import duties are regulated in Article 19 (1) of Customs Law No.10 of 1995 that the anti-dumping import duties imposed on imported goods are at most equal to the difference between the normal value and the export price of the goods with a maximum tariff of 40% (forty percent) of the customs value. Losses only occur when the import of dumped or subsidized goods causes or threatens material injury to an established industry in a country or materially impedes the growth of the industry concerned. The provisions on anti-dumping held by several countries have a valid role in the free trade system, but not if they are misused as a tool of protectionism.